The Experiences and Thoughts of Pregnant Women During COVID-19 Pandemic Regarding Pregnancy, Birth, and Postpartum Period: A Qualitative Study - ELMAS, Semra; BAŞGÖL, Şükran (Göbeklitepe Medical Science Journal, 2023)
Objective: The aim of this study is to determine the experiences and thoughts of pregnant women in the COVID -19 pandemic during the pregnancy, birth, and postpartum period. Methods: The study was conducted in a qualitative design with 10 pregnant women and a descriptive phenomenological method was used. The data were analysed using the thematic analysis technique. Results: At the end of the interview, main themes and sub-themes related to pregnancy, birth and postpartum were obtained. Themes of fear, restlessness and stress, anxiety, difficulty in follow-up, prevention/precaution themes were discovered during the pregnancy period. Themes of anxiety, loneliness, hope, prevention, and fear were determined for birth. Themes of anxiety, giving up dreams and precaution have emerged for the postpartum period. Conclusion: Results of the study will be useful to provide awareness for nurses about pregnant women’s mental health, not only about the physical health.